Business Intelligence Model using Pentaho for Academic Management at UNAMBA - Sarmiento Ponce, Hemely (2019)
The article describes the process of developing a Business Intelligence model using Pentaho, to help improve the analysis of infor-mation in the Academic Management of the National University Micaela Bastidas de Apurímac. To this end, a Data Mart was imple-mented to obtain a series of academic indicators and display the information in analytical reports and statistical graphs. The guide-lines of the Hephaestus methodology were followed to design the multidimensional database; as an analytical solution according to the information needs, OLAP online analytical processing tools were used. Pentaho Community tools such as Pentaho Data Inte-gration, Mondrian OLAP Server, Schema Workebench and Pentaho Business Analytics 7.0 were used to achieve the implementa-tion. The implementation of the Business Intelligence Model using Pentaho, allowed users immersed in academic management to visualize and analyze the behavior of academic data, so that they can make informed decisions based on the knowledge extracted from the historical information stored in the college.